Microneedle patches: the next frontier in cardiovascular care - Simran Deep Kaur; Shivanshu Choudhary; Santimoy Sen; Deepak B. Pemmaraju; Sachin Kumar Singh; Deepak N. Kapoor (Drug Delivery and Translational Research, 2025)

Improvement in Growth, Yield and Fruit Quality of Strawberry (Fragaria × ananassa Duch.) with Plant Growth Promoting Rhizobacteria - Maneesha Bhat; Amit Jasrotia; Parshant Bakshi; Mahital Jamwal; Nirmal Sharma; Arti Sharma; Deep Ji Bhat; B. K. Sinha (Applied Fruit Science, 2025)

Circulating small extracellular vesicles as blood-based biomarkers of muscle health in aging nonhuman primates - Shalini Mishra; Ashish Kumar; Yangen He; Yixin Su; Sangeeta Singh; Mark F. Santos; Rakesh Singh; Jingyun Lee; Cristina M. Furdui; Carol A. Shively; Stephen B. Kritchevsky; Thomas C. Register; et al. (GeroScience, 2024)
Age-associated loss of muscle mass and function and subsequent mobility decline define poor health outcomes, reduced quality of life, and mortality risk. The rate and extent of aging-related muscle loss varies across older adults. It is challenging to understand the molecular pathogenesis of mobility decline, as anthropometric and imaging techniques, primarily used in muscle function assessment, do not offer much molecular information. Small extracellular vesicles (sEV) are lipid membrane-bound, nano-sized (≤ 200 nm) vesicles which carry a wide array of biomolecules as their cargo. sEV contain cell/tissue-specific signatures on their surface and can be isolated from biofluids. These properties pose sEV as a minimally invasive means to monitor the functional and biological health of difficult-to-access tissues, establishing them as a promising liquid biopsy tool. Here, we first isolated skeletal muscle-derived sEV (sEV SKM ) from the serum of vervet monkeys (16 to < 25 years old) using alpha sarcoglycan (SGCA) as a muscle-specific sEV surface marker. sEV SKM were extensively characterized for size, concentration, purity, and specificity. Further, sEV SKM isolated from young (11–15 years) and old (25–29 years) monkeys’ serum were characterized for oxidized proteins by mass spectrometry and miRNAs by small-RNAseq. Notably, the analysis of oxidized proteins indicated perturbation of metabolic pathways, actin cytoskeleton, muscle cytoskeleton regulation, and HIF-1 signaling in older monkeys. Furthermore, small-RNAseq analysis identified differential expression of several miRNAs regulating metabolic pathways, inflammation, and stress signaling. Altogether, these results suggest that it is feasible to isolate sEV SKM and use them to identify molecular biomarkers that reflect the physiological state of muscle tissue.

Assessing the surface and bottom river water quality for irrigation: a study of Damodar River, India - Md. Mofizul Hoque; A. Islam; B. Sarkar; U. Deep Saha (International Journal of Energy and Water Resources, 2024)

Low-Temperature Storage Influenced the Nutritional Quality and Spoilage of Red and White Pulped Dragon Fruit - Deep Lata; C. K. Narayana; G. Karunakaran; S. Sriram; Anuradha Sane; Sachin A. J.; A. D. V. Ravi Teja; B. Maruti (Applied Fruit Science, 2024)

SOD-GIF-FIT module controls plant organ size and iron uptake - Deep Shikha; Ankit Kumar; Ajay K. Pandey; Santosh B. Satbhai (Trends in Plant Science, 2024)

Continuity between NASA MODIS Collection 6.1 and VIIRS Collection 2 land products - Miguel O. Román; Chris Justice; Ian Paynter; Peter B. Boucher; Sadashiva Devadiga; Arthur Endsley; Angela Erb; Mark Friedl; Huilin Gao; Louis Giglio; Josh M. Gray; Dorothy Hall; et al. (Remote Sensing of Environment, 2024)

A novel approach for retrieving GPP of evergreen forest regions of India using random forest regression - Deep Prakash Sarkar; B. Uma Shankar; Bikash Ranjan Parida (Remote Sensing Applications: Society and Environment, 2024)

Determination of least polluted route using Dijkstra’s algorithm - B. Deep (International Journal of Environmental Science and Technology, 2023)

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

An approach to forecast pollutants concentration with varied dispersion - B. Deep; I. Mathur; N. Joshi (International Journal of Environmental Science and Technology, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Characterization of Arsenic-Resistant Klebsiella pneumoniae RnASA11 from Contaminated Soil and Water Samples and Its Bioremediation Potential - Prahalad Kumar; Biplab Dash; Deep Chandra Suyal; S. B. Gupta; Anup Kumar Singh; Tapas Chowdhury; Ravindra Soni (Current Microbiology, 2021)

Assessment of Soil Chemical Quality, Soil Microbial Population and Plant Growth Parameters Under Organic and Conventional Rice–Wheat Cropping System - Reeta Goel; Prasenjit Debbarma; Puja Kumari; Deep Chandra Suyal; Saurabh Kumar; B. S. Mahapatra (Agricultural Research, 2021)